Knowledge, attitude, and practice toward antibiotic use among the general public in a resource-poor setting: A case of Aden-Yemen - Mohammed Alshakka; Najmaddin AH Hatem; Nazeh Al-Abd; Wafa Badullah; Shuhd Alawi; Mohamed Izham Mohamed Ibrahim (Journal of Infection in Developing Countries)
Introduction: Antibiotic overuse and misuse can cause serious health issues. These problems have contributed to a rise in bacterial resistance. Hence, our study aims to highlight the existing knowledge and attitudes toward antibiotic usage among the general public in Aden-Yemen.